Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
In order to find b1 from your formula stated we need to do few calculations
A=hb1+hb2, as you wee I multiply h with both bases( b1 and b2)
I will subtract hb2 from both sides
hb1=A-hb2
now I will divide my new expression by h
b1=(A-hb2)/h
A=hb1+hb2, as you wee I multiply h with both bases( b1 and b2)
I will subtract hb2 from both sides
hb1=A-hb2
now I will divide my new expression by h
b1=(A-hb2)/h
solve like a regular algebraic expression
A= h(b1+b2)
divide both sides by h
A/h= b1+b2
subtract b2 from both sides
A/h-b2= b1
b1= A/h-b2
hope this helps
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.